2013
DOI: 10.1890/es13-00221.1
|View full text |Cite
|
Sign up to set email alerts
|

The impact of large animal extinctions on nutrient fluxes in early river valley civilizations

Abstract: Abstract. Urbanization began independently in four river valley civilizations ;3,500-5,000 years before the present (ybp) in fertile river valleys that originally had free-ranging large animals, including elephants, that eventually went locally extinct. Such large animals are disproportionally important in the lateral spread of nutrients away from nutrient concentration gradients common near floodplains, and the local extinction of the animals would have reduced this flow of nutrients into surrounding regions.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 71 publications
0
17
0
Order By: Relevance
“…The MBMI may indicate that hunting down a size gradient has occurred over time across the region, which has been reported from studies at individual sites (e.g., Gill et al 2012. The size of remaining mammalian fauna in the forests today will likely be generally smaller; this has probably had multiple effects on ecosystem function , including changes in forest composition (Beaune et al 2013, Effiom et al 2013) and nutrient cycling (Doughty et al 2013a, b, Wolf et al 2013. Trends in both MBMI and OPI need to be interpreted carefully, especially when data from different types of hunting, e.g.…”
Section: Two Offtake Indicatorsmentioning
confidence: 89%
“…The MBMI may indicate that hunting down a size gradient has occurred over time across the region, which has been reported from studies at individual sites (e.g., Gill et al 2012. The size of remaining mammalian fauna in the forests today will likely be generally smaller; this has probably had multiple effects on ecosystem function , including changes in forest composition (Beaune et al 2013, Effiom et al 2013) and nutrient cycling (Doughty et al 2013a, b, Wolf et al 2013. Trends in both MBMI and OPI need to be interpreted carefully, especially when data from different types of hunting, e.g.…”
Section: Two Offtake Indicatorsmentioning
confidence: 89%
“…Where floodplains or parts of them still exist in protected areas, however, they act as the foci for much ecological activity. Recent modelling has suggested that large populations of mammals (Table ) were formerly responsible for redistributing large quantities of nutrients from floodplains to the surrounding landscapes (Doughty, Wolf & Malhi (,b) and that such landscapes where semblances of populations of large wild mammals still persist in national parks and game reserves were therefore much more nutrient‐rich than they are now. Of course, where the landscapes have been converted to agriculture and settlement, the use of inorganic fertiliser has vastly increased the amounts of nutrients in circulation, probably to at least an order of magnitude greater than under any natural conditions (Vitousek et al ., ; Smith, Alexander & Schwarz, ; Moss et al ., ).…”
Section: Shallow Lakes and Large Mammalsmentioning
confidence: 98%
“…The presence of an intact vertebrate fauna, accordingly, is vitally important in maintaining arthropod and other invertebrate diversity. Their presence, in addition, is important in maintaining soil nutrients and seed dispersal with flow-on effects for forest structure-and the complex of resources these present to the invertebrates (Doughty et al, 2013). There is some evidence that invertebrates decline with defaunation of megafauna due to the impact on understory vegetation and resource availability (Lamperty, Zhu, Poulsen, & Dunham, 2019) but more broadly based work is needed.…”
Section: The Importance Of Vertebrates?mentioning
confidence: 99%